Feminist Theologies: Looking Back To Look Ahead - Hunt, Mary Elisabeth (Mandrágora, 2024)
Feminist theologies in the U.S. are the reason why attention to gender has changed religions. Feminist studies in religion and social activism go hand in hand. These twin foci form a useful backdrop for understanding contemporary feminist spirituality which is a concrete coupling of religious dynamics and feminist action. That spirituality is the product of feminist work in religion and has an impact on society. Brief descriptions of a small sample of the groups that continue to deepen this work point to a bright future for feminist theologies despite backlash and obstacles.